Pembelajaran Tahfidz Al-Qur’an Metode Habituasi di Pondok Pesantren Hamalatul-Qur’an - Arifin, Muhammad Zainul (FIRDAUS, 2024)
This study discusses the habituation method of tahfidz al-Qur'an applied at the Hamalatul-Qur'an Islamic Boarding School in Jombang. The habituation method emphasizes oral skills and habituation in memorizing the Qur'an. This research is a qualitative research. Data collection is carried out through observation, interviews and documentation. The data was analyzed through reduction, verification and data analysis by checking the validity of the data through the triangulation method. The results of this study state that the concept of the habituation method is a habit of students to interact with the Qur'an by reading the Qur'an readings according to standards, so as to cause a positive response. These interactions are carried out in every activity such as muraqabah, congregational prayers and other activities. This method has its advantages and disadvantages. The advantage of this method is that students can easily and quickly memorize the Qur'an. However, the disadvantage of this method is that the activity becomes a monotonous activity that makes the students bored and lazy. For this reason, the Islamic boarding school should be able to make a variety of activities so that students do not get bored.